Heuristic Transfer in the Relationship Between Leadership and Employee Creativity. (February 2013) - McMahon, Sean R.; Ford, Cameron M.
Prior research has revealed as many as 12 leadership constructs that influence employee creativity by affecting intrinsic motivation. However, little research has explored how leaders might improve employee creativity by directly enhancing creative ability. In this article, we explore the confluence of three streams of research to establish theory supporting leader heuristic transfer (LHT) as a potential influence on employee creativity. LHT is defined as the conveyance of a leader's experience-based processes for pattern recognition, discovery, and problem solving—rules of thumb employees' may adapt for their own creative application. Using a sample of 289 employee–supervisor–coworker survey triads, results indicate that LHT has a positive relationship with employee creativity, even when controlling for established creativity-enhancing factors. Furthermore, structural equation modeling shows that LHT's influence on creativity exceeds the intrinsic motivation hypothesis central to existing constructs. Where the existing constructs focus on increasing employee intrinsic motivation in the hope that creativity occurs as a by-product, it appears that LHT boosts creativity directly, with intrinsic motivation as a positive by-product of a more capable employee.